2019
DOI: 10.1186/s13046-019-1233-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible gene 2 promotes the immune escape of hepatocellular carcinoma from nature killer cells through the interleukin-10-STAT3 signaling pathway

Abstract: Background The study examines the expression and function of hypoxia-inducible gene 2 (HIG2) in hepatocellular carcinoma (HCC) tissues and cells. Methods Forty patients with HCC were included in the study. Bioinformatic analysis was used to analyze the clinical relevance of HIG2 expression in HCC tissue samples. Immunohistochemistry was employed to determine the expression of target proteins in tumor tissues. Hepatic HepG2 and SMMC-7721 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
(30 reference statements)
0
26
0
Order By: Relevance
“…Then, we constructed the PPI network to better understand the interactions of DEGs, and the top three modules show that they were all significantly related to the pathway of immunologic and inflammatory response. CCR7 , PTPRC ( CD45 ), and IL10 were the most connected nodes in these modules, in which CCR7 was a crucial molecule in the mechanism of HCC's progression and metastasis [2729], PTPRC involved in the regulation of cytokine-induced signaling in malignancies [3032], and IL10 has been reported to increase the susceptible risk of HCC [33], decrease immunologic activity [34], and promote immune tolerance in the tumor milieu [35, 36]. Finally, survival analysis was performed to explore the potential prognostic value of 289 DEGs, and we identified 12 TME-related genes that showed significant correlation between gene expression and poor outcomes in HCC cases.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we constructed the PPI network to better understand the interactions of DEGs, and the top three modules show that they were all significantly related to the pathway of immunologic and inflammatory response. CCR7 , PTPRC ( CD45 ), and IL10 were the most connected nodes in these modules, in which CCR7 was a crucial molecule in the mechanism of HCC's progression and metastasis [2729], PTPRC involved in the regulation of cytokine-induced signaling in malignancies [3032], and IL10 has been reported to increase the susceptible risk of HCC [33], decrease immunologic activity [34], and promote immune tolerance in the tumor milieu [35, 36]. Finally, survival analysis was performed to explore the potential prognostic value of 289 DEGs, and we identified 12 TME-related genes that showed significant correlation between gene expression and poor outcomes in HCC cases.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most prevalent malignant tumors and the third most common cause of cancer-related deaths worldwide, often accompanied with invasive fast growing and metastasis [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is one of the most prevalent malignant tumors and the third most common cause of cancer-related deaths worldwide, often accompanied with invasive fast growing and metastasis [ 1 , 2 ]. Although therapeutic strategies including surgery resection, liver transplantation and radiotherapy have greatly improved [ 3 ], there are limited effective therapies for patients with advanced HCC.…”
Section: Introductionmentioning
confidence: 99%
“…50 Hypoxia has a profound effect on the NK cell infiltrate property, together with its influence on responses mediated by immune statuses in cancer tissues. 51,52 Berchem et al illustrated that microvesicles derived from tumors under hypoxia had negative regulation on the functions of NK cells through the mechanism related to transferring miR23a and TGF-β, 53 which suggested that the impaired cytotoxicity of NK cells might be induced by oxygen deficit. In brief, the prognostic gene signature developed in this study was able to accurately indicate the immunocyte infiltration degrees in high-and low-risk patients.…”
mentioning
confidence: 99%